KONSTRUKSI IDEOLOGI PEMERINTAH ATAS PRAKTIK RADIKALISME, ANARKISME DAN INTOLERAN OLEH ORMAS: SEBUAH PENDEKATAN TEKSTUAL DAN KRITIS - Ma'shumah, Nadia Khumairo (MIMESIS, 2021)
The conflict between FPI and the government forms a long story line. As a party that has legitimacy, the government has full access and power in the form of authority in determining policies, implementing law enforcement efforts and regulating access to the mass media to stem and withdraw the legality of community movements. This study seeks to identify and examine ideological construction through the production of discourse. This is echoed and rolled out by the government and the National Police in framing public perceptions of FPI. This research is a qualitative descriptive study combining the LSF theory as a conceptual framework and AWK as an analytical framework. The results of the research through analysis at the description stage, discursive practice of discourse and social practice show that the ideological construction in the discourse of 7 government restrictions on FPI on December 30, 2020 and the Chief of Police's Declaration on the Prohibition of FPI Activities on January 1, 2021 are reflected in the government's efforts to legitimize the situation by showing that there are the inequality of power that is to be perpetuated and maintained throughÂ